Prevalence of Pregnancy Associated Malaria in India - Jain, Khushi; Gupta, Palak; Balodhi, Ashutosh; Deeba, Farah; Salam, Nasir (Frontiers in Global Women's Health, 2022)
Malaria in pregnancy is a major public health concern. It results in impaired maternal health and adversely effects foetal and perinatal outcomes. The present systematic review was conducted to assess the prevalence, distribution and adverse pregnancy outcomes in malaria infected females in India. A comprehensive search and review of PubMed and Web of Science based on PRISMA guidelines was carried out to find articles reporting prevalence of malaria in pregnant women from India. Data from 16 studies were analysed and prevalence of malaria among pregnant women in India was found to be 11.4 % (95 % CI: 7.3, 16.3). Prevalence of malaria among asymptomatic and symptomatic pregnant women was found to be 10.62% (95% CI: 6.05, 16.23) and 13.13% (95% CI: 7.2, 20.52) respectively. P. falciparum and P. vivax were both reported with in the same population. The geospatial distribution of malaria in pregnancy spanned over 9 very populous states of India. The review also reported severe maternal and perinatal outcomes. Given the seriousness of malaria in pregnant women and its effects on the foetus and new-born, a stringent district wise guideline for early detection and prophylaxis in regions identified in this review will help in its better control.